The practice of spiritual criminology: a non-doing companionship for crime desistance - Amitay, Gila (International journal of offender therapy and comparative criminology, 2023)
Spiritual criminology (SC) is an umbrella term for various criminological theories, models and practices that share reference to the spiritual dimension of human existence. Informed by a growing body of research that applies spiritual approaches to various aspects of criminology, SC attempts to provide a common thread shared by most approaches to spirituality: a voluntary self-journey that begins with an elevated level of self-centeredness and is aimed at self-transformation. Based on an extensive review of the literature, this paper proposes three general principles for spiritual accompaniment of people who offended: mindful non-doing, being and acting; love and compassion; and compassionate inclusion. These principles can be applied by combining several practices: renouncing control over knowledge, process and outcomes; creating a moral atmosphere that includes forgiveness and nonjudgment; and self-modeling. SC is shown to contribute to the rehabilitation of people who offended and also to crime prevention.